Development of TCR-FC Reactive Power Compensation Device with Fuzzy Logic Control in Electric Power Networks - Sunarno, Epyk; Prasetyono, Eka; Anggriawan, Dimas Okky; Nugroho, Mochamad Ari Bagus; Eviningsih, Rachma Prilian; Suhariningsih, Suhariningsih; Nugraha, Anggara Trisna; Anggara Trisna Nugraha (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Utilization of electrical loads in predominantly inductive single-phase low-voltage power grids, the quality of electrical power becomes poor due to reactive power consumption resulting in a lack of power factor resulting in power loss, voltage drop, and decreased service life of the power grids. equipment. The research on reactive power compensation using TCR-FC aims to make improvements in improving the power factor in single-phase low-voltage electrical networks so that they have flexible control, do not experience excess compensation, have fast dynamic responses, and are space-saving. And can monitor voltage, current, and phase difference parameters through sensor readings to process data mathematically. When using electrical loads, the reactive power value is larger and the power factor is low below 0.85, the system controls the ignition angle of the TRIAC so that the current flowing into the reactor can be controlled by the reactive absorption measure of the fixed capacitor. So, it can improve the power factor. Simulation results can increase the power factor that exceeds the average value of 0.9 by 0.9797 with an error of 0.0288%. Hardware test results can increase the average power factor to exceed 0.9 by 0.9758 with an error of 0.1373%. in conclusion, reactive power compensation devices that use thyristor-controlled reactors and fixed capacitors can be more efficient than capacitor banks.